(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Forensic Odontology plays an important role in human identification when the information about the individual or mass population is unavailable. The main purpose of this study was to determine sexual dimorphism by CBCT (3-D) analysis of mental foramen among the population of Ahmedabad and Gandhinagar district in Gujarat. A Retrospective study was conducted using cone beam computed tomography of 120 subjects, of which 92 were included in the study with selection criteria. The average measurements from the superior and the inferior borders of the mental foramen to the lower border of the mandible (SBIBM and IBIBM respectively) were calculated in all age and gender groups. In this article, it shows bilateral dimorphism in the distance between SBIBM and IBIBM in both the gender groups, determining it as an effective tool for gender determination in radiology and forensic anthropology in any investigation or mass disaster cases.